The evaluation of equity in education: Proposal of instruments based on European collaboration - Serarols Boada, Jordi (Avances en Supervisión Educativa, 2018)
European countries have made the right to education universal; but it’s not enough. Education plays a key role in determining what our adult life will be like and it has been shown that an individual’s level of education correlates directly with the quality of future life. Consequently, there is a need for schools and education systems to focus on equity, as a measure of achievement, justice and opportunities to ensure that socioeconomic features, educational needs, origin and gender are compensated and that all school children can achieve the same kind of healthy lifestyle. Educational stakeholders have a key role to improve equity in education. In this context, school autonomy can boost school excellence so that the binomial equity and excellence contributes to all schoolchildren have the same opportunities to access a high-quality education. These reasons led the Inspectorate of Education of Catalonia to coordinate an Erasmus + project to promote the evaluation of equity in schools, based on raising the awareness of school leaders. Thanks to the shared practical knowledge on different educational systems, several institutions from five European countries agreed a working framework based on a new definition of school equity. From this definition, 6 dimensions and 25 sub-dimensions were established, which were defined using a rubric with four levels of achievement. This rubric, along with a dashboard of indicators, allows schools to carry out a self-assessment of school equity from which they can establish improvement proposals to make progress in their path towards quality.